Characterization of Graphene/Epoxy Nanocomposites - Malik Rashid Khasheet; Estabraq Talib Abdullah (Iraqi Journal of Physics)
Graphene nanoplatelets have received extensive attention from the scientific community in the 21st century because of their two-dimensional planar structure, high surface area, functionalization abilities, and remarkable electrical, mechanical, and thermal properties. In this work, the fabrications of graphene platelets/epoxy nanocomposites, with weight ratios of (0.002, 0.004, 0.006, and 0.008), were synthesized by the combined action of centrifuge and sonication techniques to reduce the aggregation and agglomeration of the graphene. Fourier-transform infrared spectroscopy (FTIR) verifies the prepared samples by the presence of main, distinguishing peaks associated with vibrational groups. Scanning electron microscopic (SEM) shows a good dispersion of the graphene in the epoxy, where it is homogeneously dispersed by exhibiting less agglomeration and aggregation. Atomic force microscopy (AFM) shows the average Ra value of the epoxy resin was 29 nm. In comparison, the graphene-based composites were less than 5 nm, significantly decreasing the surface roughness by adding a small amount of nanofillers. Surface roughness shows that epoxy is more rough than nanocomposites